(untitled) (International Journal of Built Environment and Sustainability, 2025)
The concept of place quality emerged from the social indicators movement, which emphasizes the significance of social issues. Accordingly, place quality encompasses not merely the quality of the physical environment but also the quality of the social environment. However, sets of indicators to measure quality in urban spaces mostly focus on the quality of the physical environment. In this context, the aim of the present study is to create a place quality indicator set, which includes indicators about the relationship of society with the urban space emphasizing the social dimensions of place quality. For this aim, a two-stage process was conducted in the study. In the first stage of the study, a conceptual reading was performed on place to be able to identify the social dimensions of place quality. According to the results of this study, the social dimension of place is associated with the concepts of "experience", "identity" and "belonging". In this context, in order to be able to discuss place quality, it is necessary to talk about the indicators that will promote spatial experience, sustain continuity of identity in space, and ensure spatial belonging. In this scope, in the second stage, in studies which contain quality indicators in the urban space, those regarding the social dimension of place were sought. A systematic literature review was performed in the Web of Science database for the selection of studies to be examined. Sixteen sources with the highest association with the subject were determined among the 209 sources. Content analysis was used in evaluating the sources. As a result of the content analysis conducted by the MAXQDA 2022 software, a total of 30 indicators were created under the themes of "experience", "identity" and "belonging". The value of the study lies in the creation of a set of indicators that assess the quality of place based on the concepts of experience, identity and belonging. Moreover, the indicator set is a valuable contribution to the field as it can be utilized by both research and local government entities and is open to ongoing improvement